1997
DOI: 10.1021/bi9716480
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer in LHCII Monomers at 77K Studied by Sub-Picosecond Transient Absorption Spectroscopy

Abstract: Energy transfer from chlorophyll b (Chl b) to chlorophyll a (Chl a) in monomeric preparations of light-harvesting complex II (LHCII) from spinach was studied at 77 K using pump-probe experiments. Sub-picosecond excitation pulses centered at 650 nm were used to excite preferentially Chl b and difference absorption spectra were detected from 630 to 700 nm. Two distinct Chl b to Chl a transfer times, ∼200 fs and 3 ps, were found. A clearly distinguishable energy transfer process between Chl a molecules occurred w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
105
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 27 publications
19
105
3
Order By: Relevance
“…previously described (39), modified as in ref 40. The pigment composition of isolated samples was determined by reversephase HPLC according to the method of Faber et al (41).…”
Section: Methodsmentioning
confidence: 99%
“…previously described (39), modified as in ref 40. The pigment composition of isolated samples was determined by reversephase HPLC according to the method of Faber et al (41).…”
Section: Methodsmentioning
confidence: 99%
“…LHCII is trimeric, and each monomer contains 14 chlorophyll (Chl), six Chl-b and eight Chl-a, and four carotenoids surrounded by a protein matrix [24]. Energy rapidly transfers to the Chl-a, and fluorescence occurs out of the Chl-a band [41][42][43][44][45][46][47]. On-going efforts are focused on characterizing the changes in the excited state manifold of LHCII under conditions that mimic high light.…”
Section: Environmentally Controlled Functionalitymentioning
confidence: 99%
“…7 The former one was assigned to neoxanthin, and the peak position is close to the one for reconstituted monomeric LHCII. 33 Also, Ruban et al 5 found that the maximum of neoxanthin is located at 486 nm for trimeric LHCII from spinach. The 510 nm peak is the weakest one of the three, and it was originally assigned to violaxanthin because the amount of violaxanthin was significantly less than that of the other xanthophylls.…”
Section: Spectral Response Of Xanthophylls Upon Excitation Of Chl B Mmentioning
confidence: 99%